The inflammatory potential of diet is related to incident frailty and slow walking in older adults. Issue 1 (January 2020) - Laclaustra, Martin; Rodriguez-Artalejo, Fernando; Guallar-Castillon, Pilar; Banegas, Jose R.; Graciani, Auxiliadora; Garcia-Esquinas, Esther; Lopez-Garcia, Esther
Summary: Background: Certain foods and dietary patterns have been associated with both inflammation and frailty. As chronic inflammation may play a role in frailty and disability, we examined the association of the inflammatory potential of diet with these outcomes. Methods: Data were taken from 1948 community-dwelling individuals ≥60 years old from the Seniors-ENRICA cohort, who were recruited in 2008–2010 and followed-up through 2012. Baseline diet data, obtained with a validated diet history, was used to calculate Shivappa's Dietary Inflammatory Index (DII), an "a priori" pattern score which is based on known associations of foods and nutrients with inflammation, and Tabung's Empirical Dietary Inflammatory Index (EDII), an " a posteriori " pattern score which was statistically derived from an epidemiological study. At follow-up, incident frailty was assessed with Fried's criteria, and incident limitation in instrumental activities of daily living (IADL) with the Lawton-Brody index. Statistical analyses were performed with logistic regression, and adjusted for the main confounders. Results: Compared with individuals in the lowest tertile of DII, those in the highest tertile showed higher risk of frailty (odds ratio [OR] 2.48; 95% confidence interval [CI]: 1.42, 4.44, p-trend = 0.001) and IADL disability (OR: 1.96; 95% CI: 1.03, 3.86, p-trend = 0.035). By contrast, EDII did not show an association with these outcomes. The DII score was associated with slow gait speed, both as a low score in the Short Physical Performance Battery test (OR: 1.82; 95% CI: 1.27, 2.62, p-trend = 0.001) and as a positive Fried's criterion (OR: 1.64; 95% CI: 1.08, 2.51, p-trend = 0.021), which use different thresholds. Conclusions: DII predicted frailty and IADL while EDII did not. DII is able to measure diet healthiness in terms of physical decline in addition to avoidance of inflammation. Registered on: ClinicalTrials.gov number, NCT01133093 .